Preparation method and application of carbon-coated titanium nitride-supported nickel-based electrocatalyst
By preparing carbon-coated titanium nitride-supported nickel-based electrocatalysts, using the heterostructure of nickel nanoparticles, titanium nitride and carbon nanotubes, the problems of complex preparation process and low ammonia synthesis efficiency are solved, and the existing nickel-based catalyst preparation process is achieved. Efficient and sustainable ammonia synthesis.
Patent Information
- Application Number
- CN202410355294.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-27
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-03-27
AI Technical Summary
The existing nickel-based catalysts have complex preparation processes, high energy consumption and low ammonia synthesis efficiency, which cannot meet the needs of sustainable development.
Through molten salt etching and vapor deposition strategies, a carbon-coated titanium nitride-supported nickel-based electrocatalyst was prepared, and the heterostructure of nickel nanoparticles, titanium nitride and carbon nanotubes were used to improve catalytic activity and structural stability.
It has achieved extremely high ammonia yield and Faraday efficiency, which is 26 times that of existing nickel-based catalysts, and the electrocatalyst has excellent structural stability and cyclic performance, supporting the green and sustainable development of ammonia synthesis.
Smart Images

Figure CN118147697B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrocatalytic nitrite reduction to synthesize ammonia, and in particular to a multi-dimensional carbon-coated titanium nitride-supported nickel-based electrocatalyst and a preparation method thereof. Background Art
[0002] Ammonia is a compound with high added value and is widely used in the chemical, agricultural and pharmaceutical industries. At present, ammonia is mainly produced by the Haber-Bosch process, which is carried out at high temperatures of 300-500°C and high pressures of 40-60MPa. The huge energy consumption seriously hinders the sustainable development of ammonia synthesis. In order to promote the realization of carbon neutrality, it is urgent to find a low-energy and sustainable ammonia synthesis method. Electrocatalytic reduction of nitrite to synthesize ammonia has attracted widespread attention due to its simple operation, high safety and no pollution. It is worth noting that electrocatalytic reduction of nitrite to synthesize ammonia uses nitrite and water as raw materials, avoiding the carbon dioxide produced during the synthesis process of the traditional Haber-Bosch process. However, the complex proton-coupled electron process reduces the ammonia yield and Faraday efficiency of this technology. In order to further improve the efficiency of ammonia synthesis and reduce the energy consumption of the electrocatalytic system, it is crucial to develop a high-performance electrocatalyst for ammonia synthesis.
[0003] Nickel-based catalysts have attracted extensive research interest due to their low cost, wide resource distribution and high catalytic activity. In recent years, related technologies for the electrocatalytic reduction of nitrite to synthesize ammonia using nickel-based catalysts have also been reported. Patent CN111359615a combines calcination and electrospinning technology to prepare a nickel-doped carbon material for electrocatalytic reduction of nitrite to synthesize ammonia. However, electrospinning technology requires high voltage to generate an electrostatic field. This not only increases energy consumption and production costs, but also increases the safety risks of the experiment. In addition, the electrocatalyst prepared from this material only exhibits a 600 μg h - 1 mg cat . -1 The ammonia yield of 2.5% is far from meeting the current demand. Therefore, it is urgent to design and develop a simple, safe and efficient nickel-based electrocatalyst to improve the yield and efficiency of ammonia synthesis. Summary of the invention
[0004] In order to solve the drawbacks of nickel-based catalysts in terms of preparation process and ammonia synthesis performance, the present invention provides a preparation method and application of a carbon-coated titanium nitride-supported nickel-based electrocatalyst. The method converts the residual nickel nanoparticles after molten salt etching into a catalyst for growing carbon nanotubes and an active site for reducing nitrite through a molten salt etching and vapor deposition strategy. The electrocatalyst prepared by the present invention has fast electron transfer kinetics, abundant catalytic active sites and excellent structural stability, and exhibits an extremely high ammonia yield in the electrocatalytic nitrite reduction reaction, which is 26 times that of the reported nickel-based catalyst, which provides the possibility for the green and sustainable development of ammonia synthesis.
[0005] The technical solution of the present invention is:
[0006] A method for preparing a carbon-coated titanium nitride-supported nickel-based electrocatalyst, the method comprising the following steps:
[0007] (1) Ti3AlC2 MAX, NiCl2, NaCl and KCl were added into a mortar and ground in a glove box for 15-30 minutes to obtain a mixture;
[0008] Among them, the molar ratio of Ti3AlC2 MAX, NiCl2, NaCl and KCl is 1:3:2:2;
[0009] (2) annealing the mixture obtained in step (1) in an argon atmosphere at a temperature of 700 to 750° C. for 24 to 30 hours; then washing with deionized water and freeze-drying to obtain nickel@MXene;
[0010] (3) placing the nickel@MXene and melamine obtained in step (2) in the downstream and upstream of a tube furnace respectively, and then annealing them in an argon atmosphere at a temperature of 750 to 800° C. for 5 to 10 minutes, washing with deionized water and freeze-drying to obtain nickel@titanium nitride / carbon nanotubes;
[0011] Among them, the mass ratio of nickel@MXene to melamine is 1:10-15;
[0012] The argon gas flow rate is 10-15 scm.
[0013] The carbon-coated titanium nitride-supported nickel-based electrocatalyst prepared by the method is used for electrocatalytic reduction of nitrite to synthesize ammonia;
[0014] Specifically, the steps include: electrolyzing the electrolyte for 0.5 to 2 hours under a three-electrode system and constant voltage to obtain ammonia;
[0015] The carbon paper, Ag / AgCl and platinum wire loaded with catalyst are used as working electrode, reference electrode and counter electrode respectively; the diaphragm is Nafion 117 membrane; the electrolyte is composed of 0.1-1.0M potassium sulfate solution containing 0.01-0.10M potassium nitrate;
[0016] 0.5-1 mg of catalyst is loaded per 1 square centimeter;
[0017] All potentials are reversible hydrogen electrode (RHE), and the conversion formula is E(RHE) = E(Ag / AgCl) + 0.222 + 0.059 × pH;
[0018] The voltage range of electrolysis is -0.3V to -0.8V.
[0019] The essential features of the present invention are:
[0020] The present invention firstly anneals the Ni in the NiCl2 molten salt at high temperature in an argon atmosphere. 2+ With the Al atom in Ti3AlC2 undergoes redox reaction, where Ni 2+ The nickel@MXene is reduced to Ni nanoparticles, while Al is oxidized to AlCl3 and volatilized at high temperature, and then washed with deionized water and freeze-dried to obtain nickel@MXene. The nickel@MXene is then annealed with melamine to pyrolyze melamine at high temperature and release carbon-phase gas and nitrogen-phase gas. The carbon-phase gas is catalyzed by the residual Ni nanoparticles after molten salt etching to generate carbon nanotubes, while the nitrogen-phase gas reacts with the substrate MXene to generate titanium nitride.
[0021] The present invention cleverly transforms residual nickel nanoparticles after molten salt etching into catalysts for growing carbon nanotubes and active sites for reducing nitrite through the strategy of turning waste into treasure.
[0022] The present invention has the following beneficial effects:
[0023] 1. The preparation of the electrocatalyst of the present invention only involves a simple calcination method, which greatly simplifies the preparation process of the nickel-based catalyst and saves time and cost.
[0024] 2. The present invention uses the strategy of turning waste into treasure to cleverly use the residual nickel nanoparticles after molten salt etching as a catalyst for carbon nanotube growth and an active site for reducing nitrite, which not only avoids the treatment of metal after etching, but also effectively utilizes the characteristics of metal.
[0025] 3. Due to the existence of metal-support interaction, nickel nanoparticles in situ loaded on MXene are not easy to agglomerate during the electrocatalytic process, thereby improving the electrocatalytic activity of the material.
[0026] 4. Treating nickel@MXene with melamine can produce a MXene-derived multidimensional nickel@titanium nitride / carbon nanotube heterostructure. The two-dimensional titanium nitride is responsible for the deoxidation step in NO2RR, the zero-dimensional nickel nanoparticles are responsible for the hydrogenation step in NO2RR, and the one-dimensional carbon nanotubes can not only enhance the overall conductivity of the heterostructure, but also strengthen the structural stability of the electrocatalyst through supporting effects.
[0027] 5. Thanks to the excellent active hydrogen generation ability of nickel nanoparticles, the excellent nitrite reduction activity of titanium nitride, and the high conductivity and structural support of carbon nanotubes, nickel@titanium nitride / carbon nanotubes showed a satisfactory ammonia yield (15600 μg h) in the electrocatalytic nitrite reduction reaction. -1 mg cat . -1 ), Faraday efficiency (94.5%) and cycle stability (ammonia yield after 30 cycles is 96%). The ammonia yield of the nickel@titanium nitride / carbon nanotube electrocatalyst prepared by the present invention is 26 times that of the reported nickel-based catalyst, which provides the possibility for the green and sustainable development of ammonia synthesis. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 X-ray diffraction patterns of the electrocatalysts prepared in Example 1, Example 2 and Example 3.
[0029] Figure 2 This is a scanning electron microscope image of the electrocatalyst prepared in Example 1.
[0030] Figure 3 This is a transmission electron microscope image of the electrocatalyst prepared in Example 1.
[0031] Figure 4 This is the linear sweep voltammetry curve of the electrocatalyst prepared in Example 1 in an electrolyte.
[0032] Figure 5 The yield of ammonia synthesis of the electrocatalyst prepared in Example 1.
[0033] Figure 6 The Faraday efficiency of ammonia synthesis of the electrocatalyst prepared in Example 1.
[0034] Figure 7 Comparison of the linear sweep voltammetry curves of the electrocatalyst prepared in Example 1 before electrolysis and after 36 hours of constant voltage electrolysis.
[0035] Figure 8 The cycling stability of the electrocatalyst prepared in Example 1. DETAILED DESCRIPTION
[0036] The specific implementation steps and drawings of the present invention are described in full and clearly below. It is necessary to point out that the specific implementation of the present invention cannot be limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, other embodiments or inferences obtained without making innovative ideas should be considered to belong to the protection scope of the present invention.
[0037] The Ti3AlC2 MAX (titanium aluminum carbide) described in the present invention is a well-known material and is commercially available. The present invention uses a product of Jilin Province —— Technology Co., Ltd., but is not limited thereto.
[0038] Embodiment 1:
[0039] The specific preparation method of nickel@titanium nitride / carbon nanotube electrocatalyst is as follows:
[0040] (1) 1 g of Ti3AlC2 MAX (i.e., 0.005 mol), 1.95 g (i.e., 0.015 mol) of NiCl2, 0.6 g (i.e., 0.01 mol) of NaCl, and 0.76 g (i.e., 0.01 mol) of KCl were added to a mortar and ground thoroughly in a glove box for 20 min to obtain a uniform mixture.
[0041] (2) The mixture was transferred into a corundum boat and placed in a tube furnace. The tube furnace was sealed and filled with argon. The mixture was then annealed at 700 °C for 24 h, washed with deionized water and freeze-dried to obtain nickel@MXene.
[0042] (3) 0.5 g of nickel@MXene and 5 g of melamine were transferred into different corundum boats and placed in the downstream and upstream of the tube furnace, respectively. The argon gas flow rate was adjusted to 10 scm, and then annealed at 800 °C for 5 min. The nickel@titanium nitride / carbon nanotube heterostructures were obtained after washing with deionized water and freeze-drying.
[0043] The Ni@TiN / CNT heterostructure was analyzed using X-ray diffraction patterns. Figure 1 As shown in the figure, the characteristic peak at about 26.5° is attributed to the formation of carbon nanotubes, the characteristic peaks at 36.6°, 42.7° and 61.8° are attributed to titanium nitride derived from MXene, and the characteristic peaks at 44.3°, 51.6° and 76.1° are attributed to the (111), (200) and (220) crystal planes of nickel. The above characterization results prove the successful preparation of nickel@titanium nitride / carbon nanotube heterostructures.
[0044] The morphology of the nickel@titanium nitride / carbon nanotube heterostructure was observed using a scanning electron microscope. Figure 2As shown in the figure, MXene in situ derivatized titanium nitride under the action of melamine and grew a large number of carbon nanotubes. Nickel nanoparticles were distributed between the layers and on the surface of the heterogeneous structure and on the top of the carbon nanotubes. The dispersed carbon nanotubes can not only enhance the conductivity of the electrocatalyst, but also improve the structural stability through the supporting effect. Nickel nanoparticles and titanium nitride have a tandem catalytic effect, which effectively improves the NO2RR performance.
[0045] Transmission electron microscopy was used to further analyze the different components of the Ni@TiN / CNT heterostructure. Figure 3 As shown, carbon nanotubes and nickel nanoparticles are uniformly distributed on the titanium nitride substrate. The strongly coupled heterogeneous interface is beneficial to improving the stability of the structure and the transport dynamics of electrons.
[0046] The electrochemical performance of nickel@titanium nitride / carbon nanotube electrocatalyst was analyzed by linear sweep voltammetry. Figure 4 As shown in Figure 2, compared with Ni@TiN and Ni@MXene, Ni@TiN / CNTs exhibited the largest current density with a peak value exceeding 200 mA cm -2 , which indicates that the Ni@TiN / CNT electrocatalyst has excellent nitrite reduction activity.
[0047] The specific steps include: (1) using a three-electrode system to electrocatalyze the reduction of nitrite to synthesize ammonia on a CHI-760E electrochemical workstation, wherein a 1×1 cm 2 The carbon paper-loaded catalyst, Ag / AgCl, and platinum wire were used as the working electrode, reference electrode, and counter electrode, respectively. (2) The electrocatalytic test was carried out in an h-type electrolytic cell containing an electrolyte of 0.05M KNO2 and 0.5M K2SO4 and separated by a Nafion 117 membrane. The Nafion 117 membrane was first treated in a 5wt% H2O2 solution at 80°C for 1 hour, then soaked in deionized water for 30 minutes, then soaked in H2SO4 at 80°C for 1 hour, and finally soaked in deionized water at 80°C for 30 minutes. (3) The preparation steps of the working electrode are as follows: 10 mg of the catalyst was dispersed in a mixed solution (0.45 mL of anhydrous ethanol + 0.45 mL of deionized water + 50 μL of Nafion solution), and a uniform ink was formed after ultrasonic treatment for 1 hour. 50 μL of catalyst ink was dropped on a 1×1 cm 2 on carbon paper and dried at room temperature. (4) All potentials in this work are reversible hydrogen electrode (RHE), and the conversion formula is E(RHE) = E(Ag / AgCl) + 0.222 + 0.059 × pH. (5) The electrocatalytic system was subjected to a chronoamperometric test at different potentials for 1 hour. (6) After 1 hour of electrolysis, 2 mL of electrolyte was taken out and the ammonia in the electrolyte was qualitatively and quantitatively determined by UV spectrophotometry.
[0048] The amount of ammonia synthesis in the electrolyte after electrolysis of nickel@titanium nitride / carbon nanotube electrocatalyst at constant voltage was detected using an ultraviolet spectrophotometer. Figure 5 As shown in Figure 2, the ammonia yield of the Ni@TiN / CNT electrocatalyst at -0.8 V reached 21300 μg h -1 mg cat . -1 , which makes sustainable and large-scale ammonia synthesis possible. Figure 5 The nickel@titanium nitride / carbon nanotubes, nickel@titanium nitride and nickel@MXene involved in the electrolysis test are all loaded on carbon paper. The electrolysis system is a three-electrode system. The electrolysis instrument is a CHI-760E electrochemical workstation. The electrolysis test method is constant voltage. The constant voltage electrolysis range is the same, all -0.3V to -0.8V. The composition of the electrolyte is the same, all containing 0.05M KNO2 and 0.5M K2SO4. The instrument for measuring the ammonia yield after electrolysis is a UV spectrophotometer.
[0049] The Faradaic efficiency was calculated using the ammonia yield of the Ni@TiN / CNT electrocatalyst at different voltages. Figure 6 As shown, the Faradaic efficiency of the Ni@TiN / CNT electrocatalyst at -0.7 V is as high as 94.5%, further demonstrating its excellent selectivity for NO2RR and its ability to effectively suppress the occurrence of hydrogen evolution side reaction.
[0050] The Ni@TiN / CNT electrocatalyst was tested by linear sweep voltammetry before electrolysis and after 36 h of constant voltage electrolysis. Figure 7 As shown, the linear sweep voltammetry curve of the electrocatalyst after 36 hours of constant voltage electrolysis at -0.7 V is basically consistent with that before electrolysis, which strongly proves that the structure of the electrocatalyst remains stable during the long-term electrocatalytic process.
[0051] The ammonia yield and Faraday efficiency of the nickel@titanium nitride / carbon nanotube electrocatalyst were tested using a cyclic stability test. Figure 7 As shown, the yield and Faradaic efficiency of the electrocatalyst remained relatively stable over 30 NO2RR cycles, further indicating not only excellent NO2RR performance but also outstanding structural and electrochemical stability.
[0052] Example 2
[0053] The other steps are the same as those in Example 1, except that the annealing temperature in step (3) of Example 1 is replaced by 700° C. from 800° C., and the obtained sample is a nickel@titanium nitride heterostructure;
[0054] The nickel@titanium nitride heterostructure was analyzed using X-ray diffraction patterns. Figure 1 As shown, the characteristic peaks at 44.3°, 51.6° and 76.1° are attributed to the (111), (200) and (220) crystal planes of nickel, and the characteristic peaks at 36.6°, 42.7° and 61.8° are attributed to the titanium nitride derived from MXene. The above characterization results prove the successful preparation of nickel@titanium nitride heterostructure.
[0055] The electrochemical performance of nickel@titanium nitride electrocatalyst was analyzed by linear sweep voltammetry. Figure 4 As shown, the current density of Ni@TiN at each potential is smaller than that of Ni@TiN / CNT, indicating that the nitrite reduction activity of Ni@TiN electrocatalyst is lower than that of Ni@TiN / CNT.
[0056] The amount of ammonia synthesis in the electrolyte after electrolysis of nickel@titanium nitride electrocatalyst at different constant voltages was detected using an ultraviolet spectrophotometer. Figure 5 As shown in Figure 2, the ammonia yield of the Ni@TiN electrocatalyst at −0.8 V was 17630 μg h -1 mg cat . -1 .
[0057] The Faradaic efficiency was calculated using the ammonia yield of the nickel@titanium nitride electrocatalyst at different voltages. Figure 6 As shown, the nickel@titanium nitride electrocatalyst exhibited a Faradaic efficiency of 89% at -0.7 V.
[0058] The ammonia yield and Faradaic efficiency of the Ni@TiN heterostructure at -0.7 V were 12280 μg h -1 mg cat . -1 and 89%, both lower than nickel@titanium nitride / carbon nanotubes. Since nickel@MXene has thermal stability at 700°C, when the annealing temperature is reduced to 700°C, nickel@MXene cannot catalyze the carbon phase gas released by pyrolysis of melamine to generate carbon nanotubes. Therefore, the reason for the performance degradation of Example 2 is that the lack of carbon nanotubes reduces the conductivity of the heterostructure, thereby hindering ion diffusion and charge transfer during the electrocatalytic process.
[0059] Example 3
[0060] The other steps are the same as those in Example 1, except that the gas flow rate in step (3) of Example 1 is replaced from 10 scm to 50 scm, and the obtained sample is a nickel@MXene heterostructure;
[0061] The Ni@MXene heterostructure was analyzed using X-ray diffraction patterns. Figure 1As shown in Figure 2, the characteristic peaks at 44.3°, 51.6°, and 76.1° are attributed to the (111), (200), and (220) crystal planes of nickel, and the characteristic peaks at 7.9° and 15.9° are attributed to the (002) and (004) crystal planes of MXene. The above characterization results demonstrate the successful preparation of the nickel@MXene heterostructure.
[0062] The electrochemical performance of Ni@MXene electrocatalyst was analyzed by linear sweep voltammetry. Figure 4 As shown, the current density of Ni@MXene at each potential is smaller than that of Ni@TiN / CNTs, indicating that the nitrite reduction activity of Ni@MXene electrocatalyst is lower than that of Ni@TiN / CNTs.
[0063] The amount of ammonia synthesis in the electrolyte after electrolysis of nickel@MXene electrocatalyst at different constant voltages was detected using an ultraviolet spectrophotometer. Figure 5 As shown in Figure 2, the Ni@MXene electrocatalyst exhibited a high energy density of 11790 μg h at −0.8 V. -1 mg cat . -1 ammonia yield.
[0064] The Faradaic efficiency was calculated using the ammonia yield of the Ni@MXene electrocatalyst at different voltages. Figure 6 As shown, the Faradaic efficiency of the Ni@MXene electrocatalyst at −0.7 V is only 74%.
[0065] The ammonia yield and Faradaic efficiency of Ni@MXene at −0.7 V were 9460 μg h -1 mg cat . -1 and 74%, which is far inferior to nickel@titanium nitride / carbon nanotubes. The faster gas flow speed causes the gas released by melamine pyrolysis to stay in the tube furnace for too short a time. These released gases are blown out of the tube furnace by the argon gas flow before reacting with nickel@MXene. Therefore, the reason for the performance degradation of Example 3 is that the lack of titanium nitride slows down the deoxidation process in the electrocatalytic nitrite reduction reaction, thereby hindering the conversion of nitrogen-containing intermediates into ammonia.
[0066] Example 4
[0067] The other steps are the same as those in Example 1, except that the annealing temperature in step (3) of Example 1 is replaced from 800° C. to 750° C.;
[0068] The obtained material properties are close;
[0069] Example 5
[0070] The other steps are the same as those in Example 1, except that the air flow rate in step (3) of Example 1 is replaced from 10 scm to 15 scm;
[0071] The obtained material properties are close;
[0072] In summary, the electrocatalyst prepared by the present invention solves the common problems of nickel-based catalysts currently used for NO2RR. As a novel electrocatalyst, nickel@titanium nitride / carbon nanotubes have fast electron transfer kinetics, abundant catalytic active sites and excellent structural stability. Thanks to the excellent active hydrogen generation ability of nickel nanoparticles, the excellent nitrite reduction activity of titanium nitride, and the high conductivity and structural support of carbon nanotubes, the nickel@titanium nitride / carbon nanotube heterostructure exhibits satisfactory ammonia yield, Faraday efficiency and cycle stability in the electrocatalytic nitrite reduction reaction, providing the possibility for the green and sustainable development of ammonia synthesis.
[0073] The above contents are only examples and explanations of the concept of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.
[0074] Matters not covered by the present invention are known technologies.
Claims
1. A method for preparing a carbon-coated titanium nitride-supported nickel-based electrocatalyst, characterized in that The method comprises the following steps: (1) grinding Ti3AlC2 MAX, NiCl2, NaCl and KCl in a glove box for 15-30 minutes to obtain a mixture; Among them, the molar ratio of Ti3AlC2 MAX, NiCl2, NaCl and KCl is 1:3:2:2; (2) annealing the mixture obtained in step (1) in an argon atmosphere at a temperature of 700-750° C. for 24-30 hours; then washing with deionized water and freeze-drying to obtain nickel@MXene; (3) placing the nickel@MXene and melamine obtained in step (2) in the downstream and upstream of a tube furnace respectively, and then annealing them in an argon atmosphere at a temperature of 750-800° C. for 5-10 minutes, washing with deionized water and freeze-drying to obtain nickel@titanium nitride / carbon nanotubes; Among them, the mass ratio of nickel@MXene to melamine is 1:10~15; The argon atmosphere in step (3) has a gas flow rate of 10 to 15 scm.
2. The use of the carbon-coated titanium nitride-supported nickel-based electrocatalyst prepared by the method of claim 1, characterized in that it is used for electrocatalytic reduction of nitrite to synthesize ammonia.
3. The use according to claim 2, characterized in that it specifically comprises the following steps: electrolyzing the electrolyte for 0.5 to 2 hours under a three-electrode system and constant voltage to obtain ammonia; in, Carbon paper loaded with catalyst, Ag / AgCl, and platinum wire were used as working electrode, reference electrode, and counter electrode, respectively; the diaphragm was Nafion 117 membrane; the electrolyte was composed of 0.1-1.0 M potassium sulfate solution containing 0.01-0.10 M potassium nitrate; 0.5~1mg catalyst is loaded per 1cm2; The voltage range of electrolysis is -0.3V to -0.8V.
Citation Information
Patent Citations
Doped carbon material catalyst as well as preparation method and application thereof
CN111359615A
Catalyst for electrochemically synthesizing ammonia and preparing method thereof
CN106111201A
Process for the Electrochemical Synthesis of Ammonia (NH3) and the Ammonia Produced Thereby
US20230279562A1